The effect of hematocrit on assay bias when using DBS samples for the quantitative bioanalysis of drugs. (August 2010) - Denniff, Philip; Spooner, Neil
Background: As hematocrit levels are known to vary between individuals and with disease state, its effect on the physical characteristics of dried blood spot (DBS) samples and on the accurate quantification of analytes within these samples is examined.Results: The area of DBS samples decreases with increasing hematocrit levels in a linear manner on the three cellulose paper substrates tested. Furthermore, a bias was observed in the concentrations of two analytes determined in DBS samples at different hematocrits, which in some cases exceeded acceptable values, particularly for hematocrits outside normal values.Conclusion: If it is expected that the hematocrit of study samples will vary from values considered normal, then its effect on the quantitative determination of an analyte in DBS samples should be investigated as part of the method development and validation. If an unacceptable effect is observed, then this will need to be addressed, by modification of the analytical method, or the inclusion of quality control samples at different hematocrit levels to show control of the assay.